4.376   x (1− x3)y′(x ) = 2x− (1− 4x3)y(x)

ODE

x(1− x3)y′(x) = 2x − (1 − 4x3)y(x )

ODE Classification

[_linear]

Book solution method
Linear ODE

Mathematica
cpu = 0.010793 (sec), leaf count = 21

{ {             }}
          c1 +-x2
   y(x) → x − x4

Maple
cpu = 0.006 (sec), leaf count = 21

{                }
  y(x) = −-x2 +-C1
          x4 − x

Mathematica raw input

DSolve[x*(1 - x^3)*y'[x] == 2*x - (1 - 4*x^3)*y[x],y[x],x]

Mathematica raw output

{{y[x] -> (x^2 + C[1])/(x - x^4)}}

Maple raw input

dsolve(x*(-x^3+1)*diff(y(x),x) = 2*x-(-4*x^3+1)*y(x), y(x),'implicit')

Maple raw output

y(x) = (-x^2+_C1)/(x^4-x)